PERSONAL NORM AND PRO-ENVIRONMENTAL CONSUMER BEHAVIOR: AN APPLICATION OF NORM ACTIVATION THEORY PDF - Setiawan, Budi; Afiff, Adi Zakaria; Heruwasto, Ignatius (ASEAN Marketing Journal, 2021)
Manuscript type: Research Article Research Aims: This study aims to fill the research gap from previous research regarding personal norms in explaining pro-environmental behavior, which does not involve awareness of consequences and ascription of responsibility as antecedents to activate personal norms. Therefore, this study tries to examine personal norms based on norm activation theory in explaining behavior. Design/methodology/approach: The final sample size is 300 respondents selected through purposive sampling technique. Primary data is collected through a closed-end questionnaire. Data analysis consists of two stages, namely the confirmatory factor analysis and structural equation model. Research Findings: Awareness of consequences and ascription of responsibility significantly form a personal norm as a core factor of the norm activation theory. Consumers feel that they have a moral obligation concerning the environment. Active personal norm, successfully forming both intention and actual behavior in the context of sorting out waste. In the downstream stage of consumer behavior, it will lead to becoming pro-environmental consumer behavior based on altruistic values. Theoretical Contribution/Originality: Personal norm is proven to be activated by awareness of consequences and ascription of responsibility. Active personal norm will lead to affect behavior, with or without being preceded by intention. Practitioner/Policy Implication: Social marketers can encourage consumers to behave pro-environmentally by activating the personal norm from their target audience first. Research limitation/Implications: This study was conducted in a cross-sectional period. Therefore, future studies will be more robust if the actual behavior is measured in a longitudinal period.